Pollen micromorphology of mangrove species in South Sumatera Coastal Area, Indonesia - Dalimunthe, Syadwina Hamama; Damayanto, I Putu Gede P.; Martiansyah, Irfan; Tihurua, Eka Fatmawati; Rahmawati, Kusuma; Fastanti, Fandri Sofiana; Muhaimin, Muhamad (Penerbit Universiti Kebangsaan Malaysia, 2023)
Reports indicated a global decline in mangrove forest coverage, with particularly high levels in Sumatera, Indonesia. To effectively conserve these ecosystems, additional research is essential to obtain comprehensive data. Specifically, investigating pollen variation in mangrove species in South Sumatera is critical due to the current lack of information. This study aimed to determine the pollen morphology of various mangrove species in South Sumatera. Fieldwork was conducted around mangrove ecosystem area of Musi Estuary in Tanjung Api-api and Payung Island, South Sumatera. Each mature flower was placed in an envelope and stored an airproof container with silica gel. Herbarium specimens were also used for identification purpose. Pollens of nine mangrove species (Avicennia alba, A. marina, Bruguiera gymnorhiza, B. sexangula, Excoecaria agallocha, Kandelia candel, Nypa fruticans, Rhizophora apiculata, and Sonneratia caseolaris) were observed with a scanning electron microscope (SEM). Pollen SEM images were measured and morphological characteristics of pollens were recorded. The pollen of mangroves in South Sumatera coastal area varied in size (small and medium), ratio of polar/equatorial (prolate, isodiametric and oblate), shape (ellipse, triangular, triangular pyramid and spheroidal shape), polar view (circular, open semi-angular and intruding semi-angular), equatorial view (prolate-circular oval, spherical-apiculate and spherical-circular oval), outline (lobate, triangular and circular), aperture (tricolporate, triporate and monosulcate) and ornamentation (perforate, psilate, echinate reticulate and gemmate). The pollen morphology has been demonstrated to be effective in distinguishing various mangrove species in South Sumatera, and it can be used to produce a species identification key.